Post-Transcriptional Regulation of Immunological Responses through Riboclustering - Nooruddin eKhan; Koelina eGanguly; Jeevan eGiddaluru; Avery eAugust (Frontiers in Immunology, 2016)
Immunological programming of immune cells varies in response to changing environmental signals. This process is facilitated by modifiers that regulate the translational fate of mRNAs encoding various immune mediators, including cytokines and chemokines, which in turn determine the rapid activation, tolerance, and plasticity of the immune system. RNA-binding proteins (RBPs) recruited by the specific sequence elements in mRNA transcripts are one such modifier. These RBPs form RBP-RNA complexes known as Riboclusters. These riboclusters serve as RNA sorting machinery, where depending upon the composition of the ribocluster, control translation, degradation or storage of mRNA. Recent findings suggest that this regulation of mRNA homeostasis is critical for controlling the immune response. Here, we present the current knowledge of the ribocluster-mediated post-transcriptional regulation of immune mediators, and highlight recent findings regarding their implications for the pathogenesis of acute or chronic inflammatory diseases.